Evaluation of the Surface Roughness of Resin Composites before and after Applying Different Bleaching Materials - Elmarakby, Ahmed; Merwah, Mohamad; Alghamdi, Mohamad; Albaitouni, Faisal; Alshreef, Mohammed; Alkahtani, Fahad (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Background: Bleaching is a conservative treatment and has been shown to be both efficient and safe but the effects of bleaching on teeth and dental materials have been studied in several studies. Objective: The aim of the current study was to evaluate the surface roughness of resin composites before and after applying different bleaching materials. Material and method: Three types of resin composites were used in this in vitro study. Two types of bleaching techniques were used: in office and at home bleach. Sixteen specimens of each resin composite type were fabricated and used in this study. Surface roughness of the samples was measured using a profilometer (Talysurf CLI 1000, Leicester, England). The surface roughness measurements and data were statistically analyzed using the one-way ANOVA and Tukey’s tests through SPSS version 21 (SPSS Inc. Chicago, IL, USA). The assessment of surface roughness was done using one-way ANOVA and Tukey’s post hoc tests. P < 0.05 was considered statistically significant. Results: The assessment of surface roughness by one-way ANOVA and Tukey’s post hoc tests showed significant differences for composite material types as well as an interaction between these parameters for each tested bleaching gels (P<.05). Conclusion: The composition of both resin composite and bleaching material play an important role in initiation and conduction of surface roughness at the outer surface of resin composite restoration.